Ranking of Snack Attributes Among Parents in a Minority Community. Issue 4 (July 2022) - Rusmevichientong, Pimbucha; Chandler, Laura; Nguyen, Kristie; Jaynes, Jessica
Abstract : Parents play a critical role in snack selection among younger children. Given the prevalence of childhood obesity and the critical role parents play was their children's eating behaviors, the purpose of this study was to explore parents' ranking of snack nutritional ingredients and snack factors. One hundred thirty-three parents of elementary school students from a predominately Asian and Hispanic population participated in the study. The results indicated that the "nutritional ingredient", protein, had the highest weighted average rank, followed by whole grain, calories, sugar, and salt. Among the snack factors, healthiness had the highest weighted average rank, followed by taste, convenience, price, and social influence. The findings from this study can enhance children's healthy eating behaviors at home by lending better understanding of the snack attributes related to parents' choices. In addition, these findings provide implications for health and nutrition professionals in the field.